Brilliant start-up : how successful entrepreneurs set up and run a brilliant business - Woods, Caspian (Brilliant., 2011)
The new edition of this brilliant bestseller gives full support through every step of the way of starting a business, making the whole process easier, so you remain inspired and on the road to success. Author Caspian Woods is a renowned entrepreneur and this book includes his vast experience of starting businesses, coaching new start-ups and interviewing hundreds of successful entrepreneurs from Bob Geldof to Phillip Green. You will learn how to: * feel positive, energised and enthused * be clear about the start-up process * be able to tailor it to suit their individual needs * know which part.